Redescription of Eidophasia concinnella Christoph, 1888 (Lepidoptera, Plutellidae), with the designation of a lectotype - Baraniak, Edward; Sinev, Sergey Yu. (Zootaxa, 2023)
Eidophasia concinnella Christoph, 1888 is redescribed and illustrated, and a lectotype is designated. A diagnostic summary with illustrations of the female genitalia is given for E. concinnella and its two most similar congeners, E. syenitella (Herrich-Schäffer, [1854]) and E. zukowskyi Amsel, 1938.